DO ENGINEERING STUDENTS FEAR THE BLANK PAGE? - Rosnani, Ismail; Nurul Nadia, Muhammad; Siti Norzaimalina, Abd Majid (Pusat Bahasa Moden (PBM), 2025)
Have you ever stared at a blank white page and felt your heart pound loudly, your palms sweat, and your mind scream, "Aah... Scary, not today!"? Turns out, you’re not alone. For many Diploma engineering students, writing essays in English feels like the ultimate battle. The authors explore deeper into this anxiety-ridden world of academic writing, shedding light on why these tech-savvy minds struggle when it comes to penning their thoughts onto paper.